Kontribusi Kepemimpinan Moderat Berlandaskan Tri Kaya Parisudha, Sikap Sosial, Dan Kemampuan Kerjasama Terhadap Kinerja Pegawai di STAHN Mpu Kuturan Singaraja - I Gede Suwindia; Ni Nyoman Kurnia Wati (Jayapangus Press, 2021)
The progress of an institution, especially a university, is strongly influenced by the performance of its employees. Employee performance is the ability of employees to perform certain skills. Good and bad employee performance can be influenced by many factors, but in this study the contribution of employee performance will be studied based on moderate leadership factors based on Tri Kaya Parisudha, social attitudes, and cooperative abilities. The purpose of this study was to determine how much the contribution of moderate leadership based on Tri Kaya Parisudha, social attitudes, and cooperation skills to the performance of employees at STAHN Mpu Kuturan Singaraja, either separately or together. This type of research is ex-post facto research and is included in causal research. The population of this study were all employees in the STAHN Mpu Kuturan Singaraja, totaling 77 people. Because the population in this study was not too large, all populations were immediately used as research samples. The instrument used to measure the research variables was a moderate leadership questionnaire based on Tri Kaya Parisudha, social attitudes, collaboration skills, and employee performance at STAHN Mpu Kuturan Singaraja. The data collected from this study were processed using multiple regression and partial correlation techniques. Based on the results of data analysis, it can be concluded that there is a significant contribution of moderate leadership based on Tri Kaya Parisudha, social attitudes, and cooperation skills on employee performance at STAHN Mpu Kuturan Singaraja.